(untitled) (Nexo Revista Científica, 2022)
In social networks, depending on the settings established in the user profile, anyone can see personal information; this includes very personal data, such as who the relatives are, their place of work, and the school they attend, among others. The more information shared, the greater the risk of compromising the profile on a Social Network, which could cause being exposed to extortion, harassment, violation of privacy, usurpation of profile or identity, among other dangers due to the inappropriate use of social networks on the Internet. In this work, a program was developed, with which, through the Application Programming Interface (API) of a social network such as Twitter, it will be possible to know from which device or application the publication was made, until knowing the place and the date that publication was made.